Analysis of Student Suicide Cases in Electronic Media: Perspectives and Roles of Islamic Education - Jihad, Fauzan Addinul; Azani, Mohammad Zakki (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The study focused on a spike in suicide rates among college students highlighted in electronic media. The goal is to identify the problems faced by college students as well as how these problems contribute to the emergence of suicidal ideation as an escape option. With qualitative methods through literature studies, this research explores data from various sources such as journals, articles, and related papers. A sociological approach was used to emphasize the need for serious treatment of the problem of suicide among college students. Furthermore, this study confirms the importance of spiritual aspects in the social context as a key to suicide prevention. The concept of Islam-based science, Iman, and Ihsan as a prevention strategy from suicide and depression. These efforts are expected to strengthen social integration, improve mental well-being, and overcome suicides so that it becomes a very crucial discussion in this framework.